Non-invasive multimodality imaging directly shows TRPM4 inhibition ameliorates stroke reperfusion injury - Chen, Bo (2019)
The transient receptor potential melastatin 4 (TRPM4) channel has been suggested to play a key role in the treatment of ischemic stroke. However, in vivo evaluation of TRPM4 channel, in particular by direct channel suppression, is lacking. In this study, we used multimodal imaging to assess edema formation and quantify the amount of metabolically functional brain salvaged after a rat model of stroke reperfusion. TRPM4 upregulation in endothelium emerges as early as 2 h post-stroke induction. Expression of TRPM4 channel was suppressed directly in vivo by treatment with siRNA; scrambled siRNA was used as a control. T2-weighted MRI suggests that TRPM4 inhibition successfully reduces edema by 30% and concomitantly salvages functionally active brain, measured by 18F-FDG-PET. These in vivo imaging results correlate well with post-mortem 2,3,5-triphenyltetrazolium chloride (TTC) staining which exhibits a 34.9% reduction in infarct volume after siRNA treatment. Furthermore, in a permanent stroke model, large areas of brain tissue displayed both edema and significant reductions in metabolic activity which was not shown in transient models with or without TRPM4 inhibition, indicating that tissue salvaged by TRPM4 inhibition during stroke reperfusion may survive. Evans Blue extravasation and hemoglobin quantification in the ipsilateral hemisphere were greatly reduced, suggesting that TRPM4 inhibition can improve BBB integrity after ischemic stroke reperfusion. Our results support the use of TRPM4 blocker for early stroke reperfusion.